2016
DOI: 10.1055/s-0042-112032
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided drainage of abdominal fluid collections after pancreatic surgery: Efficacy and long-term follow-up

Abstract: EUS-GD is an effective, minimally invasive and safe method for therapy of POFC after pancreatic surgery offering long-term remission in about 95 % of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…However, these studies reported varying etiologies of postoperative fluid collection, pseudocysts, and several methods of drainage. [1617181920] Regardless, endoscopic drainage was preferred over percutaneous drainage because percutaneous drainage led to a lower quality of life due to the external drain[2122] and the risk of permanent pancreaticocutaneous fistula in 25% of cases. [2324] Studies investigating endoscopic treatment of post-pancreatectomy fluid collection have focused on transpapillary drainage;[25] however, this technique has limited efficacy due to the limitation of the size of the pancreatic stent used.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies reported varying etiologies of postoperative fluid collection, pseudocysts, and several methods of drainage. [1617181920] Regardless, endoscopic drainage was preferred over percutaneous drainage because percutaneous drainage led to a lower quality of life due to the external drain[2122] and the risk of permanent pancreaticocutaneous fistula in 25% of cases. [2324] Studies investigating endoscopic treatment of post-pancreatectomy fluid collection have focused on transpapillary drainage;[25] however, this technique has limited efficacy due to the limitation of the size of the pancreatic stent used.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies were included in the final analysis. [1789232425262728293031] Out of the 13 studies, 10 studies provided data on the use of EUS in POPFC management (EUS-POPFC)[18924252627282930] and 6 provided data on the use of PCD in POPFC (PCD-POPFC). [789232731]…”
Section: Resultsmentioning
confidence: 99%
“…All 13 studies were of retrospective nature. [1789232425262728293031] Out of the included 13 studies, none were population based. Two studies[2728] were from multicenter data and rest were from single center.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations